Development and validation of a LC-MS/MS method for the establishment of reference intervals and biological variation for five plasma steroid hormones - van der Veen, Anna; van Faassen, Martijn; de Jong, Wilhelmina H.A.; van Beek, André P.; Dijck-Brouwer, D.A. Janneke; Kema, Ido P. (Clinical biochemistry, 2019)
With liquid chromatography–tandem mass spectrometry (LC-MS/MS) increasingly being used for the quantification of steroid hormones, there is a need for studies that re-establish reference intervals and biological variation in well-defined cohorts. A plasma steroid hormone profiling method using LC-MS/MS for quantification of progesterone, 17-hydroxyprogesterone, androstenedione, testosterone and dihydrotestosterone was developed and validated. For reference interval assessment, 280 well-characterized healthy subjects from the LifeLines cohort were selected, including 40 women using oral contraceptive pills (OCP). The biological variation was examined in 30 healthy individuals. Samples were collected over a period of 4 months with 4 week intervals. The developed method proved to be robust and sensitive. The reference interval levels in men are higher, whereas in women the levels tend to decrease with increasing age. In addition, women using OCP had lower levels of 17-OH-progesterone and androstenedione. The biological variation is generally higher in women compared to men, especially with regard to the inter-individual variation. The gender-specific determination of the reference intervals, together with the observation that the biological variation demonstrated a high degree of variation, allows interpretation of data on individual and group level for improved biochemical characterization of patients in clinical practice. This figure was created using Servier Medical Art templates, which are licensed under a Creative Commons Attribution 3.0 License, and the photo of the LC-MS/MS is from https://waters.com. [Display omitted] •The LC-MS/MS method allows high-throughput analysis of 5 plasma steroid hormones.•The fully validated method allows the quantification of dihydrotestosterone.•The reference values were established in a well-defined healthy cohort.•The novel data on biological variation shows a high degree of individual variation.